The use of a neoprene knee sleeve to compensate the deficit in knee joint position sense caused by muscle fatigue - van Tiggelen, D.; Coorevits, P.; Witvrouw, E. (Scandinavian Journal of Medicine & Science in Sports, 2008)
The importance of good proprioceptive abilities is stressed in many rehabilitation protocols. In contrast, it has been shown that muscle fatigue has a negative influence on proprioception. The objective of this study was to evaluate the effects of a neoprene knee sleeve (NKS) on the joint position sense in a fatigued knee joint. Sixty-four healthy subjects underwent four successive assessments of the same active joint repositioning test (AJRT) in an open kinetic chain setting under different conditions. First, each subject performed the AJRT without brace. One knee was braced during the second assessment. Subjects wore the brace for 6 h and were submitted to a fatigue protocol, followed by the third assessment under the same conditions as the previous one. The fourth and last AJRT was performed immediately after the third one but both knees were non-braced. When the subjects wore an NKS, significant differences in repositioning error were demonstrated between both sides. On the braced side, no significant differences were observed between the baseline assessment and the third assessment. NKS compensate the deficit in joint position sense due to fatigue. The use of NKS could be justified as a preventive measure or treatment in subjects to enhance proprioception.